2003
DOI: 10.1016/s0987-7053(03)00029-7
|View full text |Cite
|
Sign up to set email alerts
|

Time course of motor excitability before and after a task-related movement

Abstract: Aims of the study. -The time course of motor excitability during a task-related unilateral right thumb movement was studied using sub-threshold transcranial magnetic stimulation (TMS) to the contralateral left motor cortex. The level of stimulation evoked a motor evoked potential (MEP) in the thumb when the subject was at rest in approximately 10% of the trials.Methods. -Subjects made a brief right thumb movement to the predictable omission of regularly presented tone bursts allowing experimental definition of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
2
15
0
Order By: Relevance
“…Based on the state and frequency dependency of tACS effects (Feurra et al, 2013; Neuling et al, 2013; Santarnecchi et al, 2013) and the well recognized distinct patterns of changes in beta and gamma frequency power as well as cortical excitability during movement preparation (Pfurtscheller and Lopes da Silva, 1999; Reynolds and Ashby, 1999; Zaaroor et al, 2003; Muthukumaraswamy, 2010), here, for the first time, we also evaluated whether externally driving oscillatory activity at these frequencies can lead to plastic changes in cortical excitability, as indexed during movement preparation. We did not find any after-effect of tACS on these measures.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the state and frequency dependency of tACS effects (Feurra et al, 2013; Neuling et al, 2013; Santarnecchi et al, 2013) and the well recognized distinct patterns of changes in beta and gamma frequency power as well as cortical excitability during movement preparation (Pfurtscheller and Lopes da Silva, 1999; Reynolds and Ashby, 1999; Zaaroor et al, 2003; Muthukumaraswamy, 2010), here, for the first time, we also evaluated whether externally driving oscillatory activity at these frequencies can lead to plastic changes in cortical excitability, as indexed during movement preparation. We did not find any after-effect of tACS on these measures.…”
Section: Discussionmentioning
confidence: 99%
“…In this respect, Locher et al (2006) have shown that IRL could facilitate the diaphragm response to transcranial magnetic stimulation, but in a manner suggestive of a spinal rather than cortical mechanism. Because a pre‐motor negativity can facilitate the response of the target muscle to transcranial magnetic stimulation (Zaaroor et al 2003), Locher et al (2006) hypothesized that their observations could reflect increased pre‐motor inputs to the phrenic motoneurones. By confirming that the pre‐motor cortex is most likely to be involved in the compensation of inspiratory loads, the present study lends support to this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Interactions between intracortical inhibitory and excitatory processes within the primary motor cortex (M1) are crucial for motor control and change in the process of generation of a voluntary movement (at the immediate premovement stage). [4][5][6][7][8][9][10][11] GABAergically mediated short intracortical inhibition (SICI) can be studied using a wellestablished paired pulse transcranial magnetic stimulation (TMS) method. 12 Previous work demonstrated premovement modulation of SICI, characterized by a release from inhibition (disinhibition) prior to the onset of a voluntary movement in healthy subjects.…”
mentioning
confidence: 99%
“…12 Previous work demonstrated premovement modulation of SICI, characterized by a release from inhibition (disinhibition) prior to the onset of a voluntary movement in healthy subjects. [7][8][9] The ability to evaluate SICI in association with performance of a voluntary movement added another perspective to our understanding of intracortical inhibitory circuits and, in fact, seems to enhance the specificity of this technique for some pathologic states of the central motor system. For example, in patients with dystonia, premovement SICI and SICI at rest showed substantially different effects with reduction in SICI at rest and persistent lack of modulation of SICI during movement preparation.…”
mentioning
confidence: 99%
See 1 more Smart Citation